The Revolutionary Character of the ’Arab Revolutions’ and How they Could Be Studied - Del Panta, Gianni (PARTECIPAZIONE E CONFLITTO, 2021)
Over the last ten years, the masses have taken to the streets in many countries of the Middle East and North Africa, determining a rapid dislocation of the mechanisms that order societies and creating the potential conditions for deep transformations. Despite this, the results have been modest. Dealing with political revolutionary movements that have failed to ignite social revolutions, scholars have questioned whether these events can be regarded as revolutions and which theoretical instruments are the most appropriate to explore a changing region. This article discusses these issues. It does so in two ways. Firstly, the article criticises the most common understandings of revolution and proposes a different interpretation of the phenomenon. This is based on a three-step strategy, which moves beyond an evolutionist interpretation of history, takes into account different dimensions of revolutions, and distinguishes different types of revolution. Secondly, to study revolutions properly, the article proposes to combine insights from both structuralist approaches and microfoundational studies. This allows to develop a moving picture of the revolutionary situation that does not overlook class and institutional aspects. Scholars can do this by scaling down the level of analysis from the outcome that revolution produces to the mechanism that puts it in motion.